2003
DOI: 10.1016/s1097-2765(03)00245-4
|View full text |Cite
|
Sign up to set email alerts
|

Acetylation of Tat Defines a CyclinT1-Independent Step in HIV Transactivation

Abstract: The HIV transcriptional activator Tat is acetylated by p300 at a single lysine residue in the TAR RNA binding domain. We have generated monoclonal and polyclonal antibodies specific for the acetylated form of Tat (AcTat). Microinjection of anti-AcTat antibodies inhibited Tat-mediated transactivation in cells. Similarly, the p300 inhibitor Lys-CoA and siRNA specific for p300 suppressed Tat transcriptional activity. Full-length synthetic AcTat bound to TAR RNA with the same affinity as unacetylated Tat, but form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
125
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 117 publications
(128 citation statements)
references
References 49 publications
3
125
0
Order By: Relevance
“…Recombinant acetyltransferase domains were prepared as described before (39,40). Incubation was performed at 30°C for 30 min in a total volume of 20 l of reaction buffer containing 50 mM HEPES, pH 8.0, 10% glycerol, 1 mM DTT, and 10 mM sodium butyrate.…”
Section: Methodsmentioning
confidence: 99%
“…Recombinant acetyltransferase domains were prepared as described before (39,40). Incubation was performed at 30°C for 30 min in a total volume of 20 l of reaction buffer containing 50 mM HEPES, pH 8.0, 10% glycerol, 1 mM DTT, and 10 mM sodium butyrate.…”
Section: Methodsmentioning
confidence: 99%
“…[32][33][34][35][36][37][38][39] In particular, D'Orso and Frankel have found that acetylation of Tat Lys28 by PCAF modulates the assembly of Tat•TAR•P-TEFb complex. 33 They also found that Asn257 in the TRM of Cyclin T1 is essential for the recognition of acetylated Tat.…”
Section: Acetylation Of Tat Lys28 and Implications For Tar Bindingmentioning
confidence: 99%
“…The mechanism by which Tat/TAR-RNA complexes regulate transcription from the HIV-1 LTR involves the concerted recruitment of a plethora of cellular factors, including p300/CREB-binding protein (p300/CBP) (18 -25), PCAF/hGCN5 (20 -22, 26 -30), P-TEFb (30 -33), SET7/SET9 methyltransferases (34), SIRT1 (35), the Brm component of the SWI/SNF chromatin-remodeling com-plex (36), and the splicing factor, SKIP (37). The Tat protein is acetylated on Lys 28 , Lys 50 , and Lys 51 by the transcriptional coactivators/acetyltransferases, p300/CBP and PCAF/hGCN5 (20 -22, 24, 27-30, 38), which has been shown to modulate Tat interactions with P-TEFb and Brm, as well as the ability of Tat for binding TAR-RNA (20,30,35,36,39). The formation of Tat/TAR-RNA/P-TEFb/PCAF complexes on the HIV-1 LTR stimulates Ser 2 -Ser 5 -phosphorylation of the RNA pol II carboxyl-terminal domain associated with increased transcriptional elongation (30,37,40).…”
mentioning
confidence: 99%